Pleiotropic effect of lipoprotein-apheresis on the soluble form of activated leukocyte cell adhesion molecule (sALCAM) in familial hypercholesterolaemia - Bauer, Rüdiger von; Oikonomou, Dimitrios; Sulaj, Alba; Kopf, Stefan; Fleming, Thomas; Nawroth, Peter Paul (Experimental and clinical endocrinology & diabetes, 2018)
Introduction/Background: Atherosclerosis is an inflammatory disorder in which several converging immune responses modulate and induce lipid accumulation in macrophages. Activated leukocyte cell adhesion molecule (ALCAM) has been described as a structural homologue of HDL-receptor and functions as a pattern recognition receptor (PRR), while its soluble form sALCAM is involved in ALCAM-dependent and -independent immune mechanisms. The aim of this study was to investigate the effect of aggressive removal of low density lipoprotein-cholesterol (LDL-C) and lipoprotein(a) (Lp [a]) by lipoprotein-apheresis (LA) on sALCAM and blood viscosity as well as to evaluate its association with lipoproteins and serum markers of inflammation.
Gesehen am 01.04.2019
Epub ahead of print